Computational methods and statistics - Elfaki, Faiz Ahmed Mohamed; Wahid, Zaharah (IIUM Press, 2015)
The book is divided into two parts; the first introduces numerical methods and while the second part presents the statistical methods that are particularly useful for students whose mathematical background is limited to basic algebra. The book explains the concepts and supporting them with many examples and applications to appeal the interests of students of diverse engineering backgrounds. This book also features the contribution of Islamic scholars with regards to the development of science and engineering. At the end of each chapter exercises are found to test students’ knowledge and comprehension of chapter content.